Brazil in the 21st century: A difficult path - Leonid M. Grigoryev (Voprosy Ekonomiki, 2021)
Brazilian economic reforms in 21st century have great importance for the international community, especially for other countries of the middle level of development. The authors believe that, in spite of all the difficulties and crises, Brazil has made a decisive step forward by reforming its social structure and retaining democracy. Social reforms (especially minimal wage) led to strengthening middle class, but also to elevating its social aspirations. At this dramatic junction the economic development of the country was aggravated by external shocks and unsuccessful budget policies. The complex interaction of social macroeconomic policies in Brazil with strong external shocks gives lessons to countries with similar characteristics. The pandemic and recession of 2020–2021 have made the path of development more complicated but there is room for optimism for Brazil in the long run.